One summer in Savannah : a novel - Harris, Terah Shelton (Sourcebooks Landmark, 2023)
"A compelling debut that glows with bittersweet heart and touching emotion, deeply interrogating questions of family, redemption, and unconditional love in the sweltering summer heat of Savannah, as two people discover what it means to truly forgive. It's been eight years since Sara Lancaster left her home in Savannah, Georgia. Eight years since her daughter, Alana, came into this world, following a terrifying sexual assault that left deep emotional wounds Sara would do anything to forget. But when Sara's father falls ill, she's forced to return home and face the ghosts of her past. While caring for her father and running his bookstore, Sara is desperate to protect her curious, outgoing, genius daughter from the Wylers, the family of the man who assaulted her. Sara thinks she can succeed--her attacker is in prison, his identical twin brother, Jacob, left town years ago, and their mother are all unaware Alana exists. But she soon learns that Jacob has also just returned to Savannah to piece together the fragments of his once-great family. And when their two worlds collide--with the type of force Sara explores in her poetry and Jacob in his astrophysics--they are drawn together in unexpected ways"--